Experimental investigation of effect of extent and position of bypass openings on performance of a single unit liquid desiccant based indirect evaporative cooler - Naveen, Pamu Raja; Pisipaty, Srinivas Kishore; Mendu, Siva Subramanyam (Teknomekanik, 2023)
In high temperature and high humidity zones, evaporative cooling is ineffective and vapour compression systems are less energy efficient. Therefore, an alternative system is highly desirable which is effective, energy efficient and enables the use of cheap and sustainable energy sources. Indirect evaporative cooling helps in retaining humidity level of air, but is less effective in attaining lower air temperatures. To mitigate this challenge, M-cycle indirect evaporative cooling system helps in achieving sub-wet bulb temperatures. In this work, performance of a novel modified indirect evaporative M-cycle cooling system assisted by 40% aqueous Li-Cl liquid desiccant is experimentally investigated against various parameters. The cooling system used in this study is a single unit system which can perform indirect evaporative cooling, liquid desiccant dehumidification and internal cooling to the liquid desiccant. With an air velocity of 1 m/s at the inlet, the introduction of openings in between inlet and exit of the cooling system has shown a maximum improvement of 19.2% in its dew point effectiveness, with unaffected dehumidification effectiveness. Furthermore, it is observed that the dew point effectiveness is decreased with the increasing distance of openings from the inlet. The investigated cooling and dehumidification system is useful as a pre-air-conditioner to conventional air-conditioning systems and also as a stand-alone air-conditioning system.